Furnitur work from home berbahan olahan sampah plastik untuk hunian sempit - Gustiawan, Ivena Meiliani; Sitindjak, Ronald H. I. (Institut Seni Indonesia Yogyakarta, 2024)
The increasing human population with limited land in urban areas encourages people to live in narrow areas such as apartments, boarding houses, flats, and other living spaces that related to the function of the furniture to be designed. Plus covid-19 virus outbreak which has entered many people to work from home (WFH). With the help of technological developments that make it possible for someone to be more flexible to work anywhere and anytime without having to be physically present at the office where they work. This way of working and lifestyle makes many people need furniture that can accommodate their work activities flexibly in narrow dwellings, using processed plastic waste as a market attraction. This design uses the design thinking method, starts from observing the introduction of the characteristics of the plastic waste recycling process, collecting data and literature related to design problems, extracting ideas, and studying the typology of similar products as a basis for determining the concept of design boundaries, and developing the resulting final design. Through the steps taken, in the end, it will produce furniture made from processed plastic waste that is of visual quality, function, and market need for narrow dwellings. So, the resulting furniture is useful and brings positive things to users.